A Novel Murine Model of a High Dose Brachytherapy-Induced Actinic Proctitis - Leite, Carlos Heli Bezerra; Lopes, Carlos Diego Holanda; Leite, Caio Abner Vitorino Gonçalves; Terceiro, Dulce Andrade; Lima, Gabriel Silva; Freitas, Jéssica Andrade; Cunha, Fernando Queiroz; Almeida, Paulo Roberto Carvalho; Wong, Deysi Viviana Tenazoa; Lima-Júnior, Roberto César Pereira (Frontiers in Oncology, 2022)
Background. Radiation proctitis affects 1-20% of cancer patients undergoing radiation exposure due to pelvic malignancies, including prostate, gynecological and rectum cancers. The patients manifest rectal discomfort, pain, discharge, and bleeding. However, the efficacy of prophylactic measures remains controversial due to the lack of adequate animal models that mimic this condition. Objective. The present study then aimed to develop a murine model of high-dose-rate (HDR) brachytherapy-induced proctitis. Material/methods. C57BL/6 male mice were subjected to HDR (radiation source: iridium-192 [Ir-192]) through a cylindrical propylene tube inserted 2 cm far from the anal verge into the rectum. The animals received radiation doses once a day for three consecutive days (fractions of 9.5 Grays [Gy]), 3.0 mm far from the applicator surface. The sham group received only the applicator with no radiation source. The survival rate was recorded, and a colonoscopy was performed to confirm the tissue lesion development. Following euthanasia, samples of the rectum were collected for histopathology, cytokines dosage (IL-6 and KC), and immunohistochemical analysis (TNF-α and COX-2). Results. HDR significantly reduced animals’ survival ten days post first radiation exposure (14% survival vs. 100% in the non-irradiated group). Day seven was then used for further investigation. Mice exposed to radiation presented with rectum injury confirmed by colonoscopy and histopathology (P < 0.05 vs. the control group). The tissue damage was accompanied by an inflammatory response, marked by increased KC and IL-6 tissue levels, and immunostaining for TNF-α and COX-2 (P < 0.05 vs. control group). Conclusions. We established a novel animal model of actinic proctitis induced by HDR brachytherapy, marked by inflammatory damage and low animal mortality.